Gaya Hidup Sehat Terhadap Kualitas Hidup Pada Usia Lanjut - Yolanda Ramadhani; Usiono (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study was to determine a healthy lifestyle on the quality of life in old age. This research aims to explore the importance of scientific work in the context of higher education through the systematic literature review method. This research method uses the literature study method.b Data collection is done by finding sources and constructing from various sources such as books, journals and research that has been done. The findings of this study show that the application of a balanced diet, regular exercise, and stress reduction techniques can improve the physical and mental health of the elderly. Individuals who adopt a healthy lifestyle show higher levels of life satisfaction, better heart health and reduced risk of disease. Social interactions and stress management strategies also play an important role in emotional well-being